Gethuk Golan: Budaya Jawa dan Daya Tarik Pariwisata Ponorogo - Ahmad Karim Maulana; Nirmala Regita Ardiati (Yayasan Literasi Sains Indonesia, 2023)
Gethuk Golan Ponorogo has significant potential to be developed as an enticing culinary tourism attraction. Beyond its delicious taste, this food item carries substantial cultural value. The objective of this research is to uncover how Gethuk Golan can become an attraction in culinary tourism and efforts to preserve the Javanese cultural values associated with this dish. The research methodology employed is qualitative descriptive. The research is conducted in the village of Golan, Sukorejo District, Ponorogo Regency, East Java. Data collection is done through techniques such as interviews, observations, and documentation. Qualitative data analysis involves in-depth exploration of the collected data. Researchers search for patterns, relationships, and findings within the data, using descriptive analysis, and then formulate conclusions. The research findings indicate that Gethuk Golan plays a significant role in Javanese culture. This reflects the importance of togetherness and cultural preservation in the context of Javanese traditions. Furthermore, the popularity of Gethuk Golan as a culinary tourism attraction has increased, particularly through modernization efforts in its presentation by culinary entrepreneurs and vendors in Ponorogo. The potential of Gethuk Golan for tourism underscores the vital role that traditional cuisine can play in promoting local culture, supporting the regional economy, and attracting tourists.